Temperature and composition of Saturn's polar hot spots and hexagon. - Fletcher, L; Irwin, P; Orton, G; Teanby, N; Achterberg, R; Bjoraker, G; Read, P; Simon-Miller, A; Howett, C; de Kok, R; Bowles, N; Calcutt, S; et al. (2008)
Saturn's poles exhibit an unexpected symmetry in hot, cyclonic polar vortices, despite huge seasonal differences in solar flux. The cores of both vortices are depleted in phosphine gas, probably resulting from subsidence of air into the troposphere. The warm cores are present throughout the upper troposphere and stratosphere at both poles. The thermal structure associated with the marked hexagonal polar jet at 77 degrees N has been observed for the first time. Both the warm cyclonic belt at 79 degrees N and the cold anticyclonic zone at 75 degrees N exhibit the hexagonal structure.